Do Environmental Factors Influence the Distributions and Diversity of Tropical Macroinvertebrate Assemblages?: A Case Study of Mae Taeng River Basin, Northern Thailand - Tagun, Rungnapa; Kunpradid, Tatporn (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 3 (2019): July-September 2019DO - 10.14456/nujst.2019.23, 2019)
Biodiversity loss caused by environmental changes has been increased year by year. The aquatic ecosystems have been impacted as habitats are modified, most likely by human activities. Few studies have examined how biological assemblages at different spatial scales are determined by environmental gradients. We aim to understand the influence of environmental factors on the distribution and diversity of macroinvertebrates in Northern Thailand. A total of 21,391 individuals belonging to 79 families in 15 orders were identified. The order Diptera is one of the most abundant taxa in this study (family Chironomidae). The cluster analysis of macroinvertebrates and environmental factors clearly divides the areas into two groups of disturbed (downstream) and undisturbed (headstream) stations. CCA results revealed that the turbidity, conductivity and BOD are the most important factors that could influence macroinvertebrate assemblages in this study. The results also provided the basic information about the ecological status as monitored by the distribution of organisms in aquatic systems. However, it is necessary to increase data reliability by continuing to monitor other biological communities in the long-term in order to define adequate strategies for diagnosing the integrity of stream ecosystems. Keywords : Macroinvertebrate diversity; Environmental factors; Spatial distribution